Pengabdian Masyarakat Melalui Taman Bacaan Model Kampung Literasi Di Desa Rindu Hati, Bengkulu Tengah - Arono, Arono; Diani, Irma; Yunita, Wisma; Aulia, Ruri; Syahriman, Syahriman (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
The low literacy culture of the Indonesian people currently affects the low interest in reading and writing in the community. This service activity aims to describe and reveal the data of the illiterate community and their tendency to read and write, train the public in reading and writing to the community so that they can grow their interest in reading and writing, compiling literacy into an anthology of folklore and poetry both in print and through the media. online, as well as describing responses to reflections on activities that have been carried out to provide input and action on the literacy village activity model that has been carried out. The method of service is the descriptive qualitative Tabari Unib with the APTE Model (Needs Analysis, Training, Action, and Evaluation). Community service through the Taman Bacan Rindu Hati (Tabari) Unib tends to have good interest in reading and writing but is still lacking in availability and activities. that happened. Likewise with the illiteracy of only 0.5% who are still illiterate and even then in the elderly community. For this reason, in growing interest in reading and writing, the APTE model (Needs Analysis, Training, Action, and Evaluation) is carried out so as to foster interest in reading and writing in the Rindu Hati community. The outputs of this training are that the literary works called the Antologi Sastra Rindu Hati (Asri) Unib in the form of folklore, poetry, and the origins of the names of places or villages as many as 94 works with ISBN, Tabari Unib at Rumah Gadang and Tabari Unib online. Based on this service activity, this activity is very well carried out so that it has an impact on increasing the reading and writing culture of the Rindu Hati community with the Tabari Unib.